Performance Management in Ghana’s Local Government A Case Study of Ada East District Assembly_ 2015 - Sosu, Justice (University of Ghana, 2016)
There has been an increasing interest in public management about the performance of local governments in contemporary times. It has become necessary to implement performance management policies as a way of improving performance in the public sector in general and local governments in particular. It is recognised that Metropolitan, Municipal and District Assemblies (MMDAs) play very pivotal role in the socio-economic development of areas under their jurisdictions. The first objective examined the degree to which local government managers take charge of the performance of employees. The second objective delved into the challenges facing implementation of performance management. Thirdly, the study explored how local government managers use performance information for decision making. The study followed a qualitative research approach by mainly using one-on-one face-to-face interview for data collection. It used the in-depth interview guide to enable interviewees express their views. In order to ease interpretation of results, the study analysed data gathered based on emerging themes and sub-themes of each research objectives. The study found that the use of performance management is done with the preparation of an action plan from the beginning of the year which clearly specifies tasks and responsibilities of each unit as well as individual staff. In spite of this, evidence showed that severe logistical constraints, poor capacity resulting from inadequate training workshops, poor supervision and undue interference as well as poor collaboration among departments remain key challenges. Finally, it came up that local managers’ decisions for employee trainings and recommendations for promotions as well as extra work assignment, to a large extent, are taken based on the actual performance of staff. The study concluded that in practice, performance management can achieve intended results if it is accompanied by an all-inclusive human and material resources approach interlaced into continuous of employee performance.
Thesis (M Phil) - University of Ghana 2016
Keywords: Performance Management; Public Management